LEGITIMATE PURPOSES In The INHERITANCE Of WOMEN - Abd AlHamid , Sahera (Islamic Sciences Journal, 2023)
So, Allaah says (interpretation of the meaning): "I am the one who has chosen me to do so, The inheritance system in Islamic law breaks down public wealth and does not make it stacked in the hands of people without others.